PROMOSI GIZI MELAUI METODE EMO DEMO UNTUK MERUBAH PERSEPSI IBU TENTANG MAKANAN JAJANAN BERBASIS PANGAN LOKAL - Lilik Hidayanti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
High consumption of food snacks can cause decreased of food intake of children aged 0-5 years. It is due to the children feel full so they refuse meal. Impact of this behaviour is decreasing level of energy adequacy and level of protein adequacy so eventually decreasing their nutritional status. Food snacks contain much of sucrose and salt but a little protein. In additionÂ  food snack often containsÂ  food additives and also not guaranteed of its safety. To solve this problem, mothers can make food snack by themselves from local foods. Promoting local food is very important to introduce and to increase of understanding of mother about composition and nutritional contain of local food. The aim of this activity was changing mother perception about used of local foods (breadfruit and Tilapia fish) as raw materials of food snack for children aged 0-5 years. This activity used Emo Demo method with theme â€œcheap food snack, Rich of nutritionâ€. Subjects were 30 mothers who had child aged 0-5 years and also always came to Posyandu in Sukarame, Tasikmalaya. Change of perception was measured by comparing pre test and post test results,and wilcoxon was used to analyze the difference of pre test and post test results. Mean of pre test score was 9,2 and post test score was 12,9. The result of wilcoxon test shown there was the difference of pre test and post test (p < 0,001). Based on this activity, the suggestion was to continue this activity with training so the subjects were able to make foods snack using local foods (Breadfruit and Tilapia fish) as raw materials.